Effective knowledge dissemination from universities: an evaluation of technology transfer offices and the environments in which they operate - Jansen van Rensburg, Merten Secundus (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.